Bedside Rounds in Intensive Care Units during the COVID-19 Pandemic and Beyond - Custer, Jason W.; Simone, Shari; Bhutta, Adnan T. (Journal of Pediatric Intensive Care, 2020)
A survey-based pilot study was performed to examine the feasibility of videoconferencing to facilitate multidisciplinary rounds following the initiation of strict isolation and social distancing policies in a pediatric intensive care unit (PICU). The use of a mobile workstation was implemented as the central hub for rounding at the bedside by the attending physicians, while other members of the multidisciplinary and multispecialty team joined rounds from other locations with maintaining appropriate social distance. Fifty-eight staff members who participated in videoconferencing rounds completed the postimplementation survey. Eighty-eight per cent of staff agreed that the use of videoconferencing to facilitate rounds was an effective strategy to maintain social distancing between team members during the pandemic. Sixty-four percent of staff agreed that the use of videoconferencing improved participation of the PICU team and consultants by increasing access to rounds. Over 50% of staff agreed that the use of videoconferencing improved the efficiency of rounds and team productivity. Only 4% of staff responded that videoconferencing increased the duration of rounds and 37% responded that it decreased resident and team education. Fifty-five percent of staff agreed that videoconferencing was used to promote parental participation during this pandemic month. Videoconferencing was found to be a feasible solution to safely conduct multidisciplinary rounds while maintaining social distancing, and participants found it effective without interfering with normal workflow. Incorporating videoconferencing into traditional rounding practices may be advantageous following the pandemic to improve team and family access to rounds and workflow efficiency and rounding structure.
Keywords: videoconferencing; telerounds; multidisciplinary rounds; social distancing; intensive care units